Information Management in Humanitarian Aid on the Example of the Humanitarian Emergency Telecommunications Cluster (ETC) - LANDMANN TOMASZ; ZAMIAR Zenon (2023)
The topic of the article is information management in humanitarian aid on the example of the humanitarian Emergency Telecommunications Cluster (ETC). The aim of the considerations is to establish and explain the basic principles and solutions of information management that were adopted at the level of the humanitarian Emergency Telecommunications Cluster (ETC). The research material consisted of source documents developed by partners cooperating at the ETC level, supplemented with statistical data and information from scientific literature. For the purposes of the article, research methods were used in the form of analysis of existing data (desk research), analysis of documents published on the activities of ETC, and, in auxiliary scope, logical inference based on the collected material. The analysis of the presented material allows us to conclude that various guidelines, principles, procedures and solutions in information management are used for the needs of Emergency Telecommunications Cluster ETC. They are adapted to carry out humanitarian tasks as part of preparation for threats (Preparedness) and response to crises (Emergency). ETC serves as a solution provider and service provider in the field of emergency telecommunications. The operation of the ETC is one of the ways to maintain information security when providing international humanitarian assistance.